Politicizzare le immagini per vedere la guerra. L’estetica forense di Eyal Weizman e di Forensic Architecture - Guerri, Maurizio (Mechane, 2023)
The essay focuses on the relationship between images and war in the research activities of Eyal Weizman and the Forensic Architecture group. Today, wars and images are inextricably intertwined in multiple ways. The work of Forensic Architecture consists of reconstructing through all the technologies at our disposal – especially related to images and architectural structures – events that would otherwise not exist either for us or for those reconstructing their history. These facts end up not existing, not because there are no images to testify to their existence, but because these images are systematically removed from the shared gaze of the community by the power of states. With Weizman, on the one hand we can retrace the analysis of the processes that prevent us from seeing what is happening in vast areas of the planet involved in declared or concealed wars; on the other, Forensic Architecture, through its research work in the service of international tribunals, attempts to virtually reconstruct those ‘crime scenes’ in which states with their armies or secret services are the actors. These reconstruction activities of the Forensic Architecture group can be conceived as forms of “image politicisation